STEAM-Based Sustainable Education Training: Building Health Foundations and Fostering Generation Alpha - Rosalin Yuniarti Maruf; Indra Priawan; Rahmad Lingga; Abdurrohman Septiadi; Marthin Syach Putra; Ghaida Roshuna (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service project promoted sustainable education for early childhood by integrating family health literacy and STEAM-based learning in Pangkalpinang, Bangka Belitung Islands Province, Indonesia. Recognizing that sustainable development education should begin early, the program aimed to strengthen parents’ understanding of holistic child development, combining health, creativity, and environmental awareness. Inspired by the participatory principles of Participatory Action Research (PAR), the project involved three main stages they are planning, action, and observation to foster collaboration among parents, educators, and health professionals. Held on August 30, 2025, the one-day workshop was attended by 30 mothers from diverse backgrounds. Sessions were led by a doctor as well as a lecture in the Faculty of Medicine and Health Sciences of Universitas Bangka Belitung and an early childhood educator, covering children’s health topics, which are nutrition, sleep, and screen time, and STEAM-based hands-on learning using simple household materials. Key activities included the Engineering Building Challenge, where participants, as mothers, built creative projects, and the STEAM Fair, where students from the Wonderchild STEAM class performed their STEAM projects and experiments, that presented in English. The program ran effectively and encouraged active participation, collaboration, and enthusiasm among parents. Observations showed strong interest in integrating STEAM and health principles into family routines. This initiative highlights the importance of community-based education programs in Bangka Belitung and encourages future expansion to include teachers, localized STEAM modules, and sustained collaboration among educators, parents, and health experts.